Peningkatan Keterampilan Komputer Melalui Pelatihan Instalasi Sistem Operasi Windows - Thommy Willay (Cv. Utility Project Solution, 2023)
The operating system is an application that manages all the resources contained in a computer system. The operating system in a computer system can experience interference or problems so that the computer system cannot work properly and cause the computer system to not be used by users. So what can be done is to reinstall the operating system so that the computer system can be used by users again. But many computer users do not know how to install an operating system. One of the operating systems used by computer users is the Windows operating system. This research aims to improve skills through Windows operating system installation training. By improving these skills, the training participants consisting of teenagers aged 15-20 years in Pontianak City can install the Windows operating system properly. Data analysis in this research is using quantitative data with observation method. The methods used in this service are material delivery methods and hands-on practice. The results showed that the participants experienced an increase in skills, understanding and knowledge about operating systems, especially Windows and could install the Windows operating system properly.